Surface Drainage Design for Airfields and Heliports in Arctic and Subarctic Regions. - Lobacz,Edward F; Eff,Kenneth S (1981)
This report presents engineering guidance and design criteria for drainage facilities at Army and Air Force airfields and heliports in arctic and subarctic regions. Attention is given to hydrologic criteria, icings, environmental impact, storm drains and design computer programs. A design example and a list of 40 references are included in two appendixes. (Author)